Tin paste for making tin electrode, preparation method of electrode and battery, and solar cell

By printing and curing the specially made solder paste on the surface of the conductive transition layer of the heterojunction solar cell, forming the tin electrode gate line and the soldering protective layer, the problem of poor welding stability of the tin electrode gate line solder tape is solved, and the conductivity and welding stability are significantly improved.

CN119188023BActive Publication Date: 2025-03-28GOLD STONE (FUJIAN) ENERGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411709439.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-28
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

When heterojunction solar cells use tin electrode gate lines, the welding stability of the welding tape is poor, which affects the conductivity.

Method used

A solder paste including a tin alloy component, an alcohol solvent, ethyl acetate and rosin acid is used to form a tin electrode gate line and a soldering protective layer by printing a solder paste layer on the surface of the conductive transition layer and curing at a temperature of 130°C to 220°C.

Benefits of technology

It significantly improves the welding stability of the welding tape, avoids dummy welding, improves the conductivity, and effectively protects the tin electrode from oxidation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119188023B_ABST
    Figure CN119188023B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of solar cells, and specifically relates to a method for preparing solder paste, electrodes and batteries for making tin electrodes, and a solar cell. The composition of the solder paste includes: a tin alloy component with a content of 80wt% to 94wt%, an alcohol solvent with a content of 1wt% to 5wt%, and ethyl acetate and rosin acid with a total content of 5wt% to 15wt%; the composition of the tin alloy component includes a content of 40wt% to 60wt% of tin, a first metal component with a content of 30wt% to 55wt% selected from at least one of bismuth, lead and nickel, and a second metal component with a content of 5wt% to 25wt% selected from at least one of silver and copper; the alcohol solvent includes at least one of isopropyl alcohol, ethanol and ethylene glycol. The curing temperature of the solder paste is 130℃ to 220℃. The use of solder paste significantly improves the welding stability of the solder strip and improves the conductive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of solar cells, and in particular, relates to a method for preparing solder paste for making tin electrodes, electrodes and batteries, and a solar cell. Background Art

[0002] Heterojunction solar cells are a new generation of crystalline silicon solar cells, which have the advantages of high conversion efficiency, low temperature coefficient, high bifaciality, small LID attenuation, and no PID effect.

[0003] Most of the existing heterojunction solar cells use low-temperature silver paste printing technology to make electrodes. Since the electrodes need to take into account both conductivity and weldability, the requirements for the purity of silver paste are extremely high, and the existing electrode costs are relatively high. It has been proposed to use tin electrode grid lines to replace silver electrode grid lines, but the welding stability of the welding ribbon is poor, and it is easy to have cold solder joints, which affects the conductivity.

[0004] It should be noted that this part of the present application only provides background technology related to the present application and does not necessarily constitute prior art or known technology. Summary of the invention

[0005] The purpose of this application is to overcome the defects of the prior art that when tin electrode grid lines are used in heterojunction solar cells, the welding stability of the soldering strip is poor, which affects the conductive performance, and to provide a solder paste for making tin electrodes, a method for preparing electrodes and batteries, and a solar cell, which significantly improves the welding stability of the soldering strip and improves the conductive performance.

[0006] In order to achieve the above-mentioned object, in a first aspect, the present application provides a solder paste for making a tin electrode of a heterojunction solar cell, comprising a tin alloy component, an alcohol solvent, ethyl acetate and rosin acid;

[0007] The tin alloy component includes tin, a first metal component and a second metal component, the first metal component is selected from at least one of bismuth, lead and nickel, the second metal component is selected from at least one of silver and copper, based on the total mass of the tin alloy component, the content of tin is 40wt%~60wt%, the content of the first metal component is 30wt%~55wt%, the content of the second metal component is 5wt%~25wt%, and the alcohol solvent includes at least one of isopropanol, ethanol and ethylene glycol;

[0008] Based on the total mass of the solder paste, the content of the tin alloy component is 80wt% to 94wt%, the content of the alcohol solvent is 1wt% to 5wt%, and the total content of ethyl acetate and rosin acid is 5wt% to 15wt%;

[0009] The curing temperature of the solder paste is 130°C to 220°C.

[0010] In some preferred embodiments, based on the total mass of the solder paste, the ratio of the mass content of rosin acid to the mass content of ethyl acetate is 15-50.

[0011] In some preferred embodiments, based on the total mass of the tin alloy component, the content of tin is 40wt%-50wt%, and the content of the first metal component is 30wt%-40wt%.

[0012] In some preferred embodiments, based on the total mass of the solder paste, the content of the tin alloy component is 80 wt % to 90 wt %.

[0013] In a second aspect, the present application provides a method for preparing a heterojunction solar cell electrode, comprising the following steps:

[0014] The battery of the electrode to be prepared is placed with the backlight side facing downward on a grid support carrier, wherein the grid support carrier has a hollow grid, and a conductive transition layer is deposited on the area of ​​the backlight side of the battery not covered by the grid lines to obtain a plurality of conductive transition layers, with intervals between adjacent conductive transition layers;

[0015] The solder paste described in the first aspect is used to print a solder paste layer arranged in the same direction as each corresponding conductive transition layer on the surface of each conductive transition layer to obtain a plurality of solder paste layers, wherein the width of the solder paste layer is smaller than the width of the corresponding conductive transition layer, and the solder paste layer is cured to obtain tin electrode grid lines and a soldering protective layer is obtained on the surface of the tin electrode grid lines, and the curing temperature of the curing is 130°C to 220°C.

[0016] In some preferred embodiments, the curing time of the curing is 0.5 min to 10 min.

[0017] Preferably, the curing temperature of the curing is 150°C to 180°C.

[0018] Preferably, the solder paste layer is centrally arranged along the width direction of the conductive transition layer, the deposition width of the conductive transition layer is 0.5mm~1mm, the deposition thickness is 0.05μm~0.2μm, the printing thickness of the solder paste layer is 10μm~100μm, and the printing width is 0.05mm~0.5mm.

[0019] In a third aspect, the present application provides a method for preparing a heterojunction solar cell. After a conductive film is deposited on the backlight side of the cell, a tin electrode grid line is prepared on the conductive film using the electrode preparation method described in the second aspect.

[0020] In a fourth aspect, the present application provides a heterojunction solar cell, which is prepared by the preparation method of the heterojunction solar cell described in the third aspect, and its backlight surface has a plurality of conductive transition layers, and the surface of each of the conductive transition layers is provided with tin electrode grid lines arranged in the same direction as each corresponding conductive transition layer, and the width of the tin electrode grid lines is smaller than the width of the conductive transition layer, and a flux protection layer including ethyl acetate and rosin acid covers the entire surface of the tin electrode grid lines.

[0021] The solder paste of the present application comprises a tin alloy component, an alcohol solvent, ethyl acetate and rosin acid, wherein the tin alloy component comprises tin, a first metal component and a second metal component, wherein the first metal component is selected from at least one of bismuth, lead and nickel, and the second metal component is selected from at least one of silver and copper, and the alcohol solvent comprises at least one of isopropanol, ethanol and ethylene glycol. Based on the total weight of the solder paste, the content of the tin alloy component is 80wt% to 94wt%, the content of the alcohol solvent is 1wt% to 5wt%, and the total content of ethyl acetate and rosin acid is 5wt% to 15wt%. When preparing an electrode of a heterojunction solar cell, the solder paste is applied to a position where a tin electrode is to be prepared, and is cured at a temperature of 130°C to 220°C, and the alcohol solvent in the solder paste layer evaporates. , fluid precipitation channels are generated, metal particles soften and fuse, pores are squeezed out, and extrusion force is generated, which can make ethyl acetate and rosin acid precipitate and overflow to the surface of the solder paste layer. Based on the total weight of the solder paste, the total content of ethyl acetate and rosin acid is 5wt%~15wt%, and the content of alcohol solvent is 1wt%~5wt%. The strong diffusibility of ethyl acetate, after heating, ethyl acetate promotes the flow and infiltration of rosin acid, drives the rosin acid to diffuse rapidly and evenly cover the electrode surface, and can obtain a layer of ethyl acetate and rosin acid with a thickness of 10μm~15μm, a certain thickness and uniform thickness on the entire surface of the tin electrode, which can effectively protect the tin electrode from oxidation, significantly improve the welding stability of the solder strip, avoid cold soldering, and improve the conductive performance.

[0022] The preparation method of the heterojunction solar cell electrode of the present application is to place the backlight side of the battery to be prepared with the electrode facing downward on a grid support carrier with a hollow grid, deposit it, obtain several conductive transition layers, then print a solder paste layer on the surface of each conductive transition layer, obtain several solder paste layers arranged in the same direction as each corresponding conductive transition layer, then cure the solder paste layer at a temperature of 130°C to 220°C, obtain tin electrode grid lines and obtain a soldering protective layer on the entire surface of the tin electrode grid lines. Compared with first fully coating the backlight side of the battery with a conductive transition layer, then printing the tin electrode grid lines, after curing, the soldering protective layer covers the tin electrode grid lines and the conductive transition layer near the grid lines, wet etching removes the conductive transition layer not covered by the soldering protective layer, can avoid the jagged edge of the conductive transition layer, improve the linear shape and conductivity of the electrode grid lines, significantly improve the fill factor of the battery, can avoid the damage of wet etching to other structures of the solar cell, and significantly improve the open circuit voltage and fill factor of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 It is a schematic diagram of the cross-sectional structure of forming a conductive transition layer on the backlight surface of a heterojunction cell in an embodiment of the present application.

[0025] Figure 2 It is a schematic diagram of the cross-sectional structure of an embodiment of the present application in which silver electrode grid lines are formed on the light-receiving surface of a heterojunction cell, tin electrode grid lines are formed on the conductive transition layer on the backlight surface, and the entire surface of the tin electrode grid lines and the conductive transition layer has a soldering protective layer.

[0026] Figure 3 It is a schematic diagram of the structure of forming a conductive transition layer and tin electrode grid lines on the backlight surface of a heterojunction cell in an embodiment of the present application.

[0027] Figure 4 yes Figure 3 A magnified view of the local structure.

[0028] Figure 5 It is a process flow chart of an implementation method of the present application.

[0029] Description of Reference Numerals

[0030] 1. N-type single crystal silicon wafer; 2. First intrinsic passivation layer; 3. N-type doped silicon layer; 4. First transparent conductive film; 5. Second intrinsic passivation layer; 6. P-type doped silicon layer; 7. Second transparent conductive film; 8. Conductive transition layer; 9. Silver electrode grid line; 10. Tin electrode grid line; 11. Soldering protective layer. DETAILED DESCRIPTION

[0031] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0032] The present application has found that the existing tin electrode grid wire welding strips of heterojunction solar cells have poor welding stability and are prone to cold welding, which affects the conductive performance.

[0033] In this regard, in a first aspect, the present application provides a solder paste for making a tin electrode of a heterojunction solar cell, comprising a tin alloy component, an alcohol solvent, ethyl acetate and rosin acid;

[0034] The tin alloy component includes tin, a first metal component and a second metal component, the first metal component is selected from at least one of bismuth, lead and nickel, the second metal component is selected from at least one of silver and copper, based on the total mass of the tin alloy component, the content of tin is 40wt%~60wt%, the content of the first metal component is 30wt%~55wt%, the content of the second metal component is 5wt%~25wt%, and the alcohol solvent includes at least one of isopropanol, ethanol and ethylene glycol;

[0035] Based on the total mass of the solder paste, the content of the tin alloy component is 80wt% to 94wt%, the content of the alcohol solvent is 1wt% to 5wt%, and the total content of ethyl acetate and rosin acid is 5wt% to 15wt%;

[0036] The curing temperature of the solder paste is 130°C to 220°C.

[0037] The solder paste for making tin electrodes of the present application comprises a tin alloy component, an alcohol solvent, ethyl acetate and rosin acid, wherein the alcohol solvent comprises at least one of isopropanol, ethanol and ethylene glycol. When preparing the tin electrode, the solder paste is applied to the position of the tin electrode to be prepared and solidified at a temperature of 130°C to 220°C. During solidification, the alcohol solvent will volatilize, generating a fluid precipitation channel, and the metal particles will soften and fuse, displacing the pores and generating an extrusion force, which can make ethyl acetate and rosin acid precipitate and overflow to the surface of the solder paste layer. The ethyl acetate promotes the flow and infiltration of rosin acid, and a layer comprising ethyl acetate and rosin acid can be obtained on the entire surface of the tin electrode. The protective layer comprising ethyl acetate and rosin acid can protect the tin electrode from oxidation. Among the tin alloy components, the first metal component comprising at least one selected from bismuth, lead and nickel can reduce the solidification temperature when the solder paste is used to prepare the tin electrode, and can reduce the damage of high temperature to the thin film structure of the heterojunction solar cell; the second metal component comprising at least one selected from silver and copper can help shape the tin layer, prevent the tin from flowing and collapsing, and enhance the conductivity of the tin electrode. The present application found that if ethyl acetate is not added, uneven coverage of the solder paste protective layer will be caused. If rosin acid is not added, the tin electrode and the conductive transition layer cannot be well protected, and the tin electrode and the conductive transition layer are oxidized. If the tin alloy composition does not contain the first metal component, the solder paste curing temperature will be too high, and the heterojunction solar cell will be damaged by high-temperature passivation. If the tin alloy composition does not contain the second metal component, poor shaping and insufficient conductivity will occur during curing. If the solder paste is cured at a temperature lower than 130°C, the metal particles in the solder paste cannot be melted, resulting in low conductivity, and ethyl acetate and rosin acid cannot be fully precipitated and overflowed. If the solder paste is cured at a temperature higher than 220°C, high-temperature passivation damage will be caused to the heterojunction solar cell.

[0038] The present application further finds that by setting the composition of the tin alloy components within the above range, the total mass of the solder paste is used as a reference, the content of the tin alloy components, the content of the alcohol solvent, and the total content of ethyl acetate and rosin acid are set within the above range, and a protective layer including ethyl acetate and rosin acid with a thickness of 10 μm to 15 μm, a certain thickness and uniform thickness can be obtained on the entire surface of the tin electrode, which can effectively protect the tin electrode from oxidation, significantly improve the welding stability of the solder strip, avoid cold soldering, and improve the conductive performance. The present application finds that if the composition of the tin alloy components deviates from this range, the melting point and conductivity of the tin alloy will not meet the requirements of the heterojunction solar cell. If the content of the tin alloy components deviates from this range, it will cause the problem of not being able to form a continuous tin alloy grid line with a good linear shape. If the content of the alcohol solvent deviates from this range, it will cause ethyl acetate and rosin acid to be unable to fully precipitate and overflow, and the viscosity of the tin alloy slurry will not meet the requirements of the printing process. If the total content of ethyl acetate and rosin acid deviates from this range, it will cause uneven diffusion coverage of the soldering protective layer, and the soldering protective layer cannot cover the entire surface of the tin electrode and has a limited thickness, causing the problem of oxidation of the tin electrode.

[0039] In some preferred embodiments, based on the total mass of the solder paste, the ratio of the mass content of rosin acid to the mass content of ethyl acetate is 15 to 50. The present application found that the ratio of the mass content of rosin acid to the mass content of ethyl acetate is not higher than 50, which is more conducive to the full flow and infiltration of rosin acid, improves the thickness uniformity of the protective layer including ethyl acetate and rosin acid, prevents the tin electrode from being oxidized, and ensures sufficient diffusion coverage. The ratio of the mass content of rosin acid to the mass content of ethyl acetate is not less than 15, which is more conducive to ensuring the coverage thickness of rosin acid, preventing the tin electrode from being oxidized and controlling the excessive diffusion of the protective layer.

[0040] In some preferred embodiments, based on the total mass of the tin alloy component, the content of tin is 40wt% to 50wt%, and the content of the first metal component is 30wt% to 40wt%. The present application has found that based on the total mass of the tin alloy component, the content of tin, the content of the first metal component and the content of the second metal component are within the above ranges, which is more conducive to the conductive contact between the tin alloy and the TCO layer of the solar cell.

[0041] In some preferred embodiments, the content of the tin alloy component is 80wt% to 90wt% based on the total mass of the solder paste. The present application has found that, based on the total mass of the solder paste, the content of the tin alloy component, the content of the alcohol solvent, and the total content of ethyl acetate and rosin acid are within the above ranges, which is more conducive to the diffusion coverage of the soldering protective layer.

[0042] In a second aspect, the present application provides a method for preparing a heterojunction solar cell electrode, comprising the following steps:

[0043] The battery of the electrode to be prepared is placed with the backlight side facing downward on a grid support carrier, wherein the grid support carrier has a hollow grid, and a conductive transition layer is deposited on the area of ​​the backlight side of the battery not covered by the grid lines to obtain a plurality of conductive transition layers, with intervals between adjacent conductive transition layers;

[0044] The solder paste described in the first aspect is used to print a solder paste layer arranged in the same direction as each corresponding conductive transition layer on the surface of each conductive transition layer to obtain a plurality of solder paste layers, wherein the width of the solder paste layer is smaller than the width of the corresponding conductive transition layer, and the solder paste layer is cured to obtain tin electrode grid lines and a soldering protective layer is obtained on the surface of the tin electrode grid lines, and the curing temperature of the curing is 130°C to 220°C.

[0045] The preparation method of the heterojunction solar cell electrode of the present application prints a plurality of solder paste layers on the surface of the conductive transition layer, and cures the solder paste layers at a curing temperature of 130°C to 220°C, so that tin electrode grid lines can be obtained and a protective layer including ethyl acetate and rosin acid with a certain thickness and uniform thickness can be obtained on the entire surface of the tin electrode grid lines. The protective layer can effectively protect the tin electrode from oxidation, significantly improve the welding stability of the solder strip, avoid cold soldering, and improve the conductive performance.

[0046] Among them, a plurality of conductive transition layers are deposited directly on the backlight side of the battery to be prepared with the grid support carrier, compared with first coating the backlight side of the battery with the conductive transition layer, then printing the tin electrode grid line, and then covering the tin electrode grid line and the conductive transition layer near the grid line with the soldering protective layer after curing, and removing the conductive transition layer not covered by the soldering protective layer by wet etching, which can avoid the jagged edge of the conductive transition layer, can significantly improve the conductivity of the battery grid line, can avoid the damage of wet etching to other structures of the solar cell, and significantly improve the open circuit voltage VOC and fill factor FF of the battery. It can reduce the cost of electrode production by reducing the cost of wet etching equipment and chemicals.

[0047] The grid support carrier of the present application is preferably a stainless steel grid support carrier.

[0048] The conductive transition layer of the present application comprises one or more of copper, nickel, aluminum, and silver. The conductive transition layer is combined with the tin layer. The conductive transition layer and the tin layer have good affinity. The conductive transition layer is used as a carrier for the attachment of the tin electrode grid line, which can improve the adhesion of the tin electrode grid line, reduce the problem of tin ball agglomeration, and improve the welding tension between the tin electrode grid line and the welding strip, which is convenient for subsequent welding strip string welding and connection. The setting of the conductive transition layer can also improve the conductivity. The width of the solder paste layer is smaller than the width of the conductive transition layer, which can avoid the overflow of the tin alloy, is more conducive to the shaping of the grid line, and restrains the tin alloy so that it will not ball up and move.

[0049] The present application does not limit the deposition method of the conductive transition layer, and specific examples thereof include PVD magnetron sputtering, evaporation, and the like.

[0050] In some preferred embodiments, the curing time of the curing is 0.5min to 10min. The present application has found that a curing time of not less than 0.5min is more conducive to the full volatilization of the alcohol solvent, the full softening and fusion of the metal particles, the generation of extrusion force, the full precipitation and overflow of ethyl acetate and rosin acid, and the formation of a layer of ethyl acetate and rosin acid with uniform thickness on the entire surface of the tin electrode. The curing time is not more than 10min, which is more conducive to controlling the line shape of the tin electrode grid line and controlling the coverage of the soldering protective layer.

[0051] Preferably, the curing temperature is 150° C. to 180° C. The present application found that the curing temperature is 150° C. to 180° C. and the curing time is 0.5 min to 10 min, which is more conducive to the volatilization of the solvent and the sufficient diffusion and coverage of the soldering protective layer.

[0052] Preferably, along the width direction of the conductive transition layer, the solder paste layer is centrally arranged, the deposition width of the conductive transition layer is 0.5 mm to 1 mm, the deposition thickness is 0.05 μm to 0.2 μm, the printing thickness of the solder paste layer is 10 μm to 100 μm, and the printing width is 0.05 mm to 0.5 mm. Under this preferred embodiment, when preparing the electrode of the heterojunction solar cell, the solder paste is applied to the position where the tin electrode is to be prepared, and cured at a temperature of 130°C to 220°C, so that a layer including ethyl acetate and rosin acid can be obtained on the entire surface of the conductive transition layer.

[0053] In a third aspect, the present application provides a method for preparing a heterojunction solar cell. After a conductive film is deposited on the backlight side of the cell, a tin electrode grid line is prepared on the conductive film using the electrode preparation method described in the second aspect.

[0054] The heterojunction solar cell prepared in the present application has a protective layer of ethyl acetate and rosin acid with a certain thickness and uniform thickness on the entire surface of the tin electrode grid line. The tin electrode is not easily oxidized, which significantly improves the welding stability of the welding strip and the conductivity. The conductive transition layer has a neat edge, which significantly improves the fill factor FF of the battery.

[0055] In a fourth aspect, the present application provides a heterojunction solar cell, which is prepared by the preparation method of the heterojunction solar cell described in the third aspect, and its backlight surface has a plurality of conductive transition layers, and the surface of each of the conductive transition layers is provided with tin electrode grid lines arranged in the same direction as each corresponding conductive transition layer, and the width of the tin electrode grid lines is smaller than the width of the conductive transition layer, and a flux protection layer including ethyl acetate and rosin acid covers the entire surface of the tin electrode grid lines.

[0056] In the heterojunction solar cell of the present application, the entire surface of the tin electrode grid line has a protective layer of ethyl acetate and rosin acid with a certain and uniform thickness. The tin electrode is not easily oxidized, which significantly improves the welding stability of the welding strip and improves the conductive performance.

[0057] The light incident surface of the heterojunction solar cell of the present application may specifically adopt a silver electrode, for example.

[0058] The embodiments of the present application are described in detail below, which are exemplary and are only used to explain the present application, and should not be construed as limiting the present application.

[0059] Example 1

[0060] A solder paste comprises a tin alloy component, isopropyl alcohol, ethyl acetate and rosin acid. The tin alloy component contains tin, bismuth and copper. Based on the total mass of the tin alloy component, the content of tin is 42wt%, the content of bismuth is 38wt%, and the content of copper is 20wt%. Based on the total mass of the solder paste, the content of the tin alloy component is 85wt%, the content of isopropyl alcohol is 3wt%, the content of ethyl acetate is 0.4wt%, the content of rosin acid is 11.6wt%, the total content of ethyl acetate and rosin acid is 12wt%, and the ratio of the mass content of rosin acid to the mass content of ethyl acetate is 29.

[0061] A method for preparing a heterojunction solar cell, referring to Figure 1~Figure 5 ,include:

[0062] Step S1: depositing a first intrinsic passivation layer 2, an N-type doped silicon layer 3 and a first transparent conductive film 4 on the light-receiving surface of an N-type monocrystalline silicon wafer 1, and depositing a second intrinsic passivation layer 5, a P-type doped silicon layer 6 and a second transparent conductive film 7 on the backlight surface, to obtain a heterojunction cell with double-sided transparent conductive films;

[0063] Step S2: Place the heterojunction cell sheet coated with double-sided transparent conductive film in step S1 on a grid support carrier with a hollow grid, with the light-receiving side facing upward and the backlight side facing downward. The grid support carrier is fitted with the backlight side of the cell. A copper conductive transition layer is deposited on the area not covered by the grid line on the backlight side of the cell by a PVD magnetron sputtering method. A plurality of conductive transition layers 8 arranged in the same direction are obtained on the backlight side of the cell. The deposition thickness of each conductive transition layer 8 is 0.08 μm to 0.12 μm, the deposition width is 0.9 mm to 1 mm, and there is a gap between adjacent conductive transition layers 8. The transition layer 8 is distributed in stripes. The aforementioned solder paste is used to print a solder paste layer on the surface of each conductive transition layer 8 in the center along the width direction of the conductive transition layer by printing, and a plurality of solder paste layers are arranged in the same direction as the corresponding conductive transition layer 8. The plurality of solder paste layers are distributed in stripes. The printing thickness of the solder paste layer is 10 μm to 15 μm, and the printing width is 0.45 mm to 0.5 mm. The solder paste layer is cured to obtain a tin electrode grid line 10 and a soldering protective layer 11 is obtained on the surface of the tin electrode grid line 10. The curing temperature is 150° C. and the curing time is 8 min.

[0064] Step S3: Print silver paste on the light-receiving surface of the heterojunction cell obtained in step S2 and solidify to obtain silver electrode grid lines 9, thereby obtaining a heterojunction solar cell having a conductive transition layer on the backlight side, tin electrode grid lines on the outer surface of the conductive transition layer on the backlight side, and silver electrode grid lines on the light-receiving side.

[0065] A heterojunction solar cell is prepared by the above-mentioned preparation method, and its backlight surface has multiple conductive transition layers arranged in the same direction, the surface of each conductive transition layer has tin electrode grid lines in the same arrangement direction as the conductive transition layer, the width of the tin electrode grid lines is smaller than the width of the conductive transition layer, and the entire surface of the tin electrode grid lines and the entire surface of the conductive transition layer are covered with a flux protection layer including ethyl acetate and rosin acid.

[0066] Example 2

[0067] The method is carried out with reference to Example 1, except that in step S2 of the method for preparing a heterojunction solar cell, the curing temperature is 130° C. and the curing time is 3 min.

[0068] Example 3

[0069] The same process is carried out with reference to Example 2, except that the curing time is 2 minutes.

[0070] Example 4

[0071] The method is carried out with reference to Example 1, except that, based on the total mass of the solder paste, the content of ethyl acetate is 0.2wt%, the content of rosin acid is 11.8wt%, and the ratio of the mass content of rosin acid to the mass content of ethyl acetate is 59.

[0072] Example 5

[0073] The method is carried out with reference to Example 1, except that, based on the total mass of the tin alloy component, the content of tin is 55wt%, the content of bismuth is 30wt%, and the content of copper is 15wt%.

[0074] Comparative Example 1

[0075] The process is carried out with reference to Example 1, except that in step S2 of the method for preparing a heterojunction solar cell, the curing temperature is 120°C.

[0076] Comparative Example 2

[0077] The method is carried out with reference to Example 1, except that, based on the total mass of the tin alloy component, the content of tin is 70wt%, the content of bismuth is 10wt%, and the content of copper is 20wt%.

[0078] Comparative Example 3

[0079] The method is carried out with reference to Example 1, except that, based on the total mass of the solder paste, the content of the tin alloy component is 93wt%, the content of isopropyl alcohol is 3wt%, the content of ethyl acetate is 0.1wt%, and the content of rosin acid is 3.9wt%.

[0080] Comparative Example 4

[0081] The method is carried out with reference to Example 1, except that the solder paste does not contain ethyl acetate, and the content of rosin acid is 12 wt % based on the total mass of the solder paste.

[0082] Comparative Example 5

[0083] The method is carried out with reference to Example 1, except that the solder paste does not contain rosin acid, and the content of ethyl acetate is 12 wt % based on the total mass of the solder paste.

[0084] Comparative Example 6

[0085] The method is carried out with reference to Example 1, except that the tin alloy component contains only tin and bismuth but no copper. Based on the total mass of the tin alloy component, the content of tin is 62wt%, and the content of bismuth is 38wt%.

[0086] Comparative Example 7

[0087] The method is carried out with reference to Example 1, except that the tin alloy component contains only tin and copper but no bismuth. Based on the total mass of the tin alloy component, the content of tin is 80wt%, and the content of copper is 20wt%.

[0088] Test Case

[0089] The average thickness and thickness uniformity of the soldering protective layer on the surface of the tin electrode grid line prepared in the above embodiment and the comparative example were tested by the step profiler test method, and the results are shown in the following table. The above embodiment and the comparative example were used to prepare heterojunction solar cells, and the prepared cells were subjected to IV tests. The test conditions were STC, and the short-circuit current Isc, open-circuit voltage Voc, fill factor FF, conversion efficiency η and maximum power PMPP in the test results were extracted for comparison. The results are shown in the following table.

[0090]

[0091] Comparing Example 1 and Example 2, the curing temperature of the curing is 150°C to 180°C, which is more conducive to the full diffusion and coverage of the soldering protective layer, improving the thickness and thickness uniformity of the soldering protective layer, and improving the filling factor, conversion efficiency, maximum power and other performances of the battery. Comparing Example 1 and Example 4, based on the total mass of the solder paste, the ratio of the mass content of rosin acid to the mass content of ethyl acetate is 15 to 50, which is more conducive to improving the thickness uniformity of the soldering protective layer, improving the filling factor, conversion efficiency, maximum power and other performances of the battery. Comparing Example 1 and Example 5, based on the total mass of the tin alloy component, the tin content is 40wt% to 50wt%, which is more conducive to improving the filling factor, conversion efficiency, maximum power and other performances of the battery.

[0092] Comparing Example 1 and the embodiment, the curing temperature is 130°C to 220°C, which can improve the filling factor, conversion efficiency, maximum power and other performance of the battery. Comparing Example 2 and the embodiment, based on the total mass of the tin alloy component, the tin content is 40wt% to 60wt%, the content of the first metal component is 30wt% to 55wt%, and the content of the second metal component is 5wt% to 25wt%, which can improve the filling factor, conversion efficiency, maximum power and other performance of the battery. Comparing Example 3 and the embodiment, based on the total mass of the solder paste, the total content of ethyl acetate and rosin acid is 5wt% to 15wt%, which can improve the thickness and thickness uniformity of the soldering protective layer, and improve the filling factor of the battery. The solder paste contains ethyl acetate, which can improve the thickness uniformity of the soldering protective layer and improve the battery's filling factor, conversion efficiency, maximum power and other performances. Comparing comparative example 4 with the embodiment, the solder paste contains ethyl acetate, which can improve the thickness uniformity of the soldering protective layer and improve the battery's filling factor, conversion efficiency, maximum power and other performances. Comparing comparative example 5 with the embodiment, the solder paste contains rosin acid, which can improve the battery's filling factor, conversion efficiency, maximum power and other performances. Comparing comparative example 6 with embodiment 1, the tin alloy component contains at least one selected from silver and copper, which can improve the battery's filling factor, conversion efficiency, maximum power and other performances. Comparing comparative example 7 with embodiment 1, the tin alloy component contains at least one selected from bismuth, lead and nickel, which can improve the battery's filling factor, conversion efficiency, maximum power and other performances.

[0093] The preferred embodiments of the present application are described in detail above, but the present application is not limited thereto. Within the technical concept of the present application, the technical solution of the present application can be subjected to a variety of simple modifications, including combining various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed in the present application and belong to the protection scope of the present application.

Claims

1. A solder paste for making tin electrodes for heterojunction solar cells, characterized in that: It includes tin alloy components, alcohol solvent, ethyl acetate and rosin acid; The tin alloy component includes tin, a first metal component and a second metal component, the first metal component is selected from at least one of bismuth, lead and nickel, the second metal component is selected from at least one of silver and copper, based on the total mass of the tin alloy component, the content of tin is 40wt%~60wt%, the content of the first metal component is 30wt%~55wt%, the content of the second metal component is 5wt%~25wt%, and the alcohol solvent includes at least one of isopropanol, ethanol and ethylene glycol; Based on the total mass of the solder paste, the content of the tin alloy component is 80wt% to 94wt%, the content of the alcohol solvent is 1wt% to 5wt%, and the total content of ethyl acetate and rosin acid is 5wt% to 15wt%; The curing temperature of the solder paste is 130° C. to 220° C.; based on the total mass of the solder paste, the ratio of the mass content of rosin acid to the mass content of ethyl acetate is 15 to 50; When the solder paste is cured at the curing temperature, the alcohol solvent evaporates to generate a fluid precipitation channel, the metal particles of the tin alloy component soften and fuse to squeeze out the pores, generating an extrusion force, ethyl acetate and rosin acid precipitate and overflow to the surface of the solder paste layer, ethyl acetate promotes the flow and infiltration of rosin acid, and a layer including ethyl acetate and rosin acid is obtained on the surface of the tin electrode.

2. The solder paste according to claim 1, characterized in that: Based on the total mass of the tin alloy component, the content of tin is 40wt%-50wt%, and the content of the first metal component is 30wt%-40wt%.

3. The solder paste according to claim 1, characterized in that: Based on the total mass of the solder paste, the content of the tin alloy component is 80wt% to 90wt%.

4. A method for preparing a heterojunction solar cell electrode, characterized in that: The following steps are involved: The battery of the electrode to be prepared is placed with the backlight side facing downward on a grid support carrier, wherein the grid support carrier has a hollow grid, and a conductive transition layer is deposited on the area of ​​the backlight side of the battery not covered by the grid lines to obtain a plurality of conductive transition layers, with intervals between adjacent conductive transition layers; The solder paste described in any one of claims 1 to 3 is used to print a solder paste layer arranged in the same direction as each corresponding conductive transition layer on the surface of each conductive transition layer to obtain a plurality of solder paste layers, wherein the width of the solder paste layer is smaller than the width of the corresponding conductive transition layer, and the solder paste layer is cured to obtain tin electrode grid lines and a soldering protective layer is obtained on the surface of the tin electrode grid lines, and the curing temperature of the curing is 130°C to 220°C.

5. The preparation method according to claim 4, characterized in that: The curing time of the curing is 0.5 min to 10 min.

6. The preparation method according to claim 5, characterized in that: The curing temperature of the curing is 150°C to 180°C.

7. The preparation method according to claim 5, characterized in that: The solder paste layer is centrally arranged along the width direction of the conductive transition layer, the deposition width of the conductive transition layer is 0.5mm~1mm, the deposition thickness is 0.05μm~0.2μm, the printing thickness of the solder paste layer is 10μm~100μm, and the printing width is 0.05mm~0.5mm.

8. A method for preparing a heterojunction solar cell, characterized in that: After a conductive film is deposited on the backlight side of the battery, a tin electrode grid line is prepared on the conductive film using the electrode preparation method described in any one of claims 4 to 7.

9. A heterojunction solar cell, characterized in that: The heterojunction solar cell is prepared by the preparation method of claim 8, wherein the backlight surface thereof has a plurality of conductive transition layers, and the surface of each of the conductive transition layers is provided with tin electrode grid lines arranged in the same direction as each corresponding conductive transition layer, the width of the tin electrode grid lines is smaller than the width of the conductive transition layer, and a soldering protective layer including ethyl acetate and rosin acid covers the entire surface of the tin electrode grid lines.

Citation Information

Patent Citations

  • Low-silver-consumption solar cell and preparation method thereof

    CN117393619A

  • Lead-free, high tin ternary solder alloy of tin, silver, and bismuth

    WO1997047425A1